Sex identification of different species of wild birds using a single universal protocol to the bird sexing method based on gene polymorphism - RudaуаS. V.; KaterynychО. О.; Drahulian, M. V.; Chaplygina, A. B.; Pakhomov, O. Y. (Regulatory Mechanisms in Biosystems, 2020)
This article presents an elaboration of the protocol for the method of sexing wild birds based on the polymorphism of the CHD gene using P2/P8 primer for Common Pheasant – Phasianus colchicus (Linnaeus, 1758; Galliformes, Phasianidae); Silver Lofur or Silver Pheasant – Lophura nycthemera (Linnaeus, 1758; Galliformes, Phasianidae), Budgerigar – Melopsittacus undulatus (Shaw, 1805; Psittaciformes, Psittacidae), Herring Gull – Larus argentatus (Pontoppidan, 1763; Charadriiformes, Laridae), and White Stork – Ciconia ciconia (Linnaeus, 1758; Ciconiiformes, Ciconiidae). Blood samples were taken from Common Pheasant, Silver Pheasant and White Stork using the “drop of blood on paper” method. For the Budgerigar and the Herring Gull, DNA was isolated from the feather follicle. To isolate DNA, a commercial NeoPrep 100 DNA reagent kit (Neogen, Ukraine) was used. Primers P2/P8 were used for PCR; PCR was performed using GenPac PCR Core reagents (Neogen, Ukraine). We selected the optimal amount of Tag polymerase, the amount of DNA and primers and, according to the amount of reagents, set acceptable amplification modes and electrophoresis agarose gel percentage. Prior to PCR, additional DNA gel electrophoresis purification is proposed, which increases the percentage of positive sex determination results. It was found that the ideal mixture for the 5 bird species was an amplification mixture (total volume 20 µL, containing 1 U Tag polymerase, 100 ng DNA and 0.6 µM of each primer). The amplified CHD-Z fragment of Common and Silver pheasants is of 340 n. p., CHD-W 360 n. p. Herring Gull and Budgerigar have 350 n. p. of CHD-Z length, and 400 n. p. of CHD-W length, White Stork has its CHD-Z of 370 n. p. long. It is advisable to investigate the genome of the experimental bird species using horizontal electrophoresis in agar’s gel with the concentration of 5%, which makes it possible to clearly visualize the female genotype. The universal protocol of the method of sex determination based on polymorphism of the CHD gene for the 5 studied bird species is described. These results of the study led to the conclusion that for the simultaneous sexing of several species of birds, it is advisable to develop a unified protocol for determining the status of the CHD gene, with the aim of clarifying the gender, as well as new approaches in ornithology and ecology aimed at determining interspecific differences associated with gene polymorphism. Identification of differences in fragment sizes may be useful for identifying the species in cases when birds form mixed pairings for taxonomic and phylogenetic comparisons.